Management Influence on Investors: Evidence from Shareholder Votes on the Frequency of Say on Pay - Ferri, Fabrizio; Oesch, David (Contemporary Accounting Research, 2016)
Abstract The literature on shareholder voting has mostly focused on the influence of proxy advisors on shareholder votes. We exploit a unique empirical setting enabling us to provide a direct estimate of management's influence. Analyzing shareholder votes on the frequency of future say on pay (SOP) votes, we find that a management recommendation for a particular frequency is associated with a 26 percent increase in voting support for that frequency. Additional tests suggest that the documented association is likely to capture a causal effect. Management influence varies across firms and is smaller at firms where perceived management credibility is lower. Compared to firms adopting an annual frequency, firms following management's recommendation to adopt a triennial frequency are significantly less likely to change their compensation practices in response to an adverse SOP vote, consistent with the notion that a less frequent vote results in lower management accountability.